Impact of Construction Delay-Controlling Parameters on Project Schedule: DEMATEL-System Dynamics Modeling Approach - Ajayi, Babatunde Oluwaseun; Chinda, Thanwadee (Frontiers in Built Environment, 2022)
Project delay has been a phenomenon contending with the construction sector opposing time, cost, and quality. This study develops the model, which is a combination of two mathematical decision-making methods DEMATEL-System dynamics modelling, to investigate the impact of the factors on the entire project schedule. The simulation results reveal the importance of minimizing Design Error to reduce the project delay at the beginning (or preconstruction stage) of the project. Rework, design changes, and change orders must also be closely monitored during the construction to ensure work productivity and on-time project completion. The results also reveal that experienced designers and use of updated design technology help reduce design errors, thus enhancing work performance in the long term. As shown in the simulation results, the actual project completion time and magnitude of delay steadily reduce with the project series. This explains the fact that the more the consistency and effectiveness in handling the delay factors as similar projects are performed in turns, the better the project performance in terms of time. Therefore, careful consideration of the delay factors reduces the time lag and delay magnitude in construction projects. Other improvements, such as effective supervision during construction which is a function of experienced supervisors, good project management and cooperation among key stakeholders, including owners, consultant, and contractors also assist in reducing the construction delay in the long term.